Effect of Career Development and Supervision on Employee Satisfaction at Pt. Kartika Swarna Dwipa (Tupperware Sales Company) - Mukmin Pohan (AIBPM Publisher, 2022)
Supervision is all the activities undertaken by the manager in an effort to ensure that the actual results in accordance with the planned results. Job satisfaction cannot be felt by employees due to the company's career development programs that are less clear and have not been able to guarantee the future of employees. The research method using quantitative approach, the type of research used descriptive quantitative. Data were collected through interviews, questionnaires and documentation studies. The data analysis used is multiple linear regression. The population used is all employees who numbered 78 people. Determination of sample in research using saturated sample that is with all employees amounted to 78 people. The results showed that career development and supervision simultaneously and partially have a positive and significant effect on employee job satisfaction with the value of determinant coefficient of 0.132 or 13,2%, while the remaining 86,8% influenced by other variables not examined. The conclusion of the research is simultaneously and partially career development and supervision have a significant effect on employee job satisfaction at PT. Kartika Swarna Dwipa (Company in Sales Tupperware).Keywords: Career Development, Supervision, Job Satisfaction